Administrative and Enforcement Issues in Collecting Assessment Rate Arrears in Local Authorities in Malaysia - Mohd, Elina; Ayub, Zainal Amin; Mohd Anuar, Haslinda (UniversityPublications.net, 2020)
The assessment rate is the main revenue for local authorities. It finances the services and maintenance of the local authority areas. The revenue is mainly from the assessment rate, but collection keeps on decreasing, causing difficulties to local authorities to provide good services. This study aims to examine factors causing assessment rate arrears. The scope of the study is on the local authorities in the northern region of Malaysia. The study employs socio-legal research where data is collected through interviews with respondents like the Mayor or Council’s President and respondents from the relevant local councils. Data is analysed using descriptive analysis. It is found that there are weaknesses in administrative and enforcement in claiming assessment rates arrears. This study proposes ways to overcome assessment rates arrears, among others, through the amendment of the Local Government Act 1976, improving local authorities’ services, cooperation by the Land Office and enhancing public perception and awareness towards assessment rates